2009
DOI: 10.1007/s11269-009-9435-0
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Water Resources for Rural Residential Development in Western Australia

Abstract: Rainwater collected from residential roofs and greywater generated from domestic uses except toilets are viewed as possible substitutes for high grade water sources which supply nonpotable indoor uses and irrigation in Australia. This paper searches for alternatives by adopting roofwater and greywater in residential envelope as per Australian water standards. A water balance model Aquacycle was applied to determine storage capacities and to evaluate the percentage reduction in water supplying, stormwater run-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 18 publications
1
38
0
3
Order By: Relevance
“…Different studies have highlighted the benefits of using harvested rainwater for toilet flushing [16,17]. Zhang et al [18] observe that harvesting all roof runoff for use in toilet flushing can reduce water consumption in residential buildings by about 25%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have highlighted the benefits of using harvested rainwater for toilet flushing [16,17]. Zhang et al [18] observe that harvesting all roof runoff for use in toilet flushing can reduce water consumption in residential buildings by about 25%.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28] and Australia [18][19][20][21][22][23][24][25][26][27][28][29]. Additional studies on RWH systems have been carried out in the Mediterranean region as well.…”
Section: Introductionmentioning
confidence: 99%
“…Two common uses for greywater are toilet flushing and lawn irrigation. Untreated greywater can be used for subsurface irrigation [56]. Grey water reuse can help to reduce reliance on traditional water sources that are under stress and it can also significantly reduce wastewater discharge [57,58].…”
Section: Grey Water Recycling and Reusementioning
confidence: 99%
“…It can potentially save a significant amount of domestic water demand [60,73,74]. An Australian study showed a savings of 12.3% to 25.1% in potable water use when harvested rainwater was used for toilet flushing and garden irrigation [56]. Moreover, this rainwater is a relatively high quality water source that can be directly used for non-potable uses, or with filtration and disinfection for potable uses [75,76].…”
Section: Rainwater Harvestingmentioning
confidence: 99%
See 1 more Smart Citation